PERAN MEKANISME GOOD CORPORATE GOVERNANCE DALAM MENCEGAH PERUSAHAAN MENGALAMI FINANCIAL DISTRESS - Fani Silviani; Djauhar Edi Purnomo; Muhamad Yusuf (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2020)
This study aimed to examine the role of the mechanism of good corporate governance in an effort to prevent the occurance of financial distress in public companies in Indonesia by using indicators of the board of directors, board of commissioners, managerial ownership, institutional ownership, independent commissioners and audit committees. The population in this study includes manufacturing companies listed on the Indonesia Stock Exchange (IDX) and continuously publishes financial report in 2015 – 2017. Determination of samples is done by purposive sampling method with the criteria of Interest Coverage Ratio. The total sample used in this study was 18 companies of observation data. This study uses logistic regression as a data analysis tool